KEANEKARAGAMAN ODONATA DI WADUK SELOREJO KABUPATEN MALANG DAN SUMBER CLANGAP KABUPATEN KEDIRI - Muhammad Azmi Dwi Susanto; Muhammad Muhibbuddin Abdillah; Zakki Mubarak (LP4MK STKIP PGRI Lubuklinggau, 2020)
The Selorejo Reservoir administratively is located in Malang district while Sumber Clangap is located in Kediri district. Both of these locations have different environmental conditions both abiotic and biotic components. Selorejo Reservoir has fewer tree canopies and the area dominated with herbs from Poaceae. Sumber Clangap has heterogeneous vegetation from trees, bush, and herbs. Odonata diversity at Waduk Selorejo is never been studied before while Odonata diversity data at Sumber Clangap needed an update. This study aims to determine the diversity of Odonata in Sumber Clangap and Selorejo Reservoir. The method used in this study is the transect belt and visual day flying to get the data type and number of Odonata. Data were analyzed used the Shannon-Wiener Index. Selorejo Reservoir has 75 individual that is divided into 2 families of Odonata. Sumber Clangap Have 399 individual that is divided into 5 families. The results showed that there were 17 species of Odonata included in six families in both locations. The data showed that the measured diversity by Shannon-Wiener Index at Sumber Clangap H' = 1.81 which is higher than the diversity of the Waduk Selorejo, H' = 1.7.